2015
DOI: 10.1103/physrevb.92.075402
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectrum of twisted bilayer graphene

Abstract: We study the electronic properties of twisted bilayers graphene in the tight-binding approximation. The interlayer hopping amplitude is modeled by a function, which depends not only on the distance between two carbon atoms, but also on the positions of neighboring atoms as well. Using the Lanczos algorithm for the numerical evaluation of eigenvalues of large sparse matrices, we calculate the bilayer single-electron spectrum for commensurate twist angles in the range 1• . We show that at certain angles θ greate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 34 publications
(144 reference statements)
8
129
0
Order By: Relevance
“…This is, however, a nontrivial task that has not been accomplished so far. Thanks to extensive studies using various methods [6,[11][12][13][14][15][16][17][18][19][20][21][22][23], the band structure of TBG at small twist angle is known to be rather complex and depends sensitively on microscopic details such as lattice relaxation. Near the socalled magic twist angle, various methods find four nearly flat minibands at low energy, but differ significantly on important features such as their bandwidth and the gap to excited bands.…”
Section: Introductionmentioning
confidence: 99%
“…This is, however, a nontrivial task that has not been accomplished so far. Thanks to extensive studies using various methods [6,[11][12][13][14][15][16][17][18][19][20][21][22][23], the band structure of TBG at small twist angle is known to be rather complex and depends sensitively on microscopic details such as lattice relaxation. Near the socalled magic twist angle, various methods find four nearly flat minibands at low energy, but differ significantly on important features such as their bandwidth and the gap to excited bands.…”
Section: Introductionmentioning
confidence: 99%
“…Both Vσ and Vπ decay rapidly when the distance between the two sites is larger than the lattice parameter a0 = 2.46 Å, and the contribution of is negligible in the interlayer hoppings in multilayer graphene [23,24]. Here we use 0.24 eV as the maximum value of (for two sites with A-A stacking, the same value as used in Ref.…”
Section: Theoreticalmentioning
confidence: 99%
“…Wong et al [16] found, besides the coexistence of moiré patterns and moiré super-superlattices, also a very rich an interesting electronic structure. Despite the fact that the electronic structure of twisted bilayer graphene has been extensively studied [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], the spatial variation of electronic structure within the unit cell of the moiré pattern did not receive a lot of attention yet.…”
Section: Introductionmentioning
confidence: 99%
“…In real materials, the difference between an incommensurate and a commensurate twist-angle is less clear, as the presence of imperfections (strain, tears, ripples) may make even a commensurate system sample Ω continuously. The effect of disorder on twisted bilayer graphene's electronic properties has begun to be investigated theoretically 20,21 , but we do not study it here.…”
Section: Formalismmentioning
confidence: 99%